Rapid Estradiol Modulation of Neuronal Connectivity and Its Implications for Disease - Srivastava, Deepak P.; Penzes, Peter (Frontiers in Endocrinology, 2011)
Estrogens have multiple actions in the brain including modulating synaptic plasticity, connectivity and cognitive behaviours. While the classical view of estrogens are as endocrine signals, whose effects manifest via the regulation of gene transcription, mounting evidence has been presented demonstrating that estrogens have rapid effects within specific areas of the brain. The emergence that 17 β-estradiol can be produced locally in the brain which can elicit rapid (within minutes) cellular responses has led to its classification as a neurosteroid. Moreover, recent studies have also begun to detail the molecular and cellular underpinnings of how 17 β-estradiol can rapidly modulate spiny synapses (dendritic spines). Remodelling of dendritic spines is a key step in the rewiring of neuronal circuitry thought to underlie the processing and storage of information in the forebrain. Conversely, abnormal remodelling of dendritic spines is thought to contribute to a number of psychiatric and neurodevelopmental disorders. Here we review recent molecular and cellular work that offers a potential mechanism of how 17 β-estradiol may modulate synapse structure and function of cortical neurons. This mechanism allows cortical neurons to respond to activity-dependent stimuli with greater efficacy. In turn this form of plasticity may provide an insight into how 17 β-estradiol can modulate the rewiring of neuronal circuits, underlying its ability to influencing cortically based behaviours. We will then go on to discuss the potential role of 17 β-estradiol modulation of neural circuits and its potential relevance for the treatment of psychiatric and neurodevelopmental disorders.